Russia on the Market of High-technology and Intellectual Services - I. G. Korotkov; V. A. Zubenko (Мир новой экономики, 2018)
As of today the exports of services from Russia take a small part in the total volume of Russia’s goods and services export. The biggest success was attained in the exports of high-technology services of State Atomic Energy Corporation “Rosatom” and in the exports of software in IT industry. The potential of the exports of the other types of high-technology and intellectual services has not been totally unlocked yet. The positions of the exports of educational services have been lost in large part and in need of recovery. There are objective preconditions in Russia for development of the exports of transport and tourism services. The rise in exports of high-technology and intellectual services can be achieved by upgrading of the intellectual property protection for the Russian organizations and individuals abroad. The other source of the rise in exports - the government support in customs and exchange regulation and the subsidy assistance of global marketing.